2019
DOI: 10.1037/apl0000421
|View full text |Cite
|
Sign up to set email alerts
|

The importance of being humble: A meta-analysis and incremental validity analysis of the relationship between honesty-humility and job performance.

Abstract: The HEXACO model presents a conceptualization of personality that includes the trait honesty-humility (H-H) in addition to 5 other personality traits (i.e., agreeableness, conscientiousness, emotionality, extraversion, openness) that closely approximate the ubiquitous five-factor model (FFM) of personality. A substantial literature has accumulated supporting the structure of the HEXACO model and the construct validity of the H-H trait in particular. A newer development is the appearance of H-H in the applied p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 85 publications
(100 reference statements)
6
88
1
Order By: Relevance
“…All studies to date also indicate that the construct assessed by integrity tests is a compound of conscientiousness, agreeableness, and emotional stability, in that order (see Ones & Viswesvaran, 2001 for summaries). Honesty-Humility correlates .55 with integrity (see meta-analytic results presented in Table 2 of Lee, Berry, Gonzalez-Mule, 2019). This is the same degree of correlation found between alternate measures of integrity .…”
Section: Conceptual Confusion and Little Incremental Validity Of The supporting
confidence: 60%
See 1 more Smart Citation
“…All studies to date also indicate that the construct assessed by integrity tests is a compound of conscientiousness, agreeableness, and emotional stability, in that order (see Ones & Viswesvaran, 2001 for summaries). Honesty-Humility correlates .55 with integrity (see meta-analytic results presented in Table 2 of Lee, Berry, Gonzalez-Mule, 2019). This is the same degree of correlation found between alternate measures of integrity .…”
Section: Conceptual Confusion and Little Incremental Validity Of The supporting
confidence: 60%
“…Big Five Agreeableness, in turn, yielded comparably weak relations with prosocial behavior in all situations. Moreover, there is now consistent, meta-analytic evidence that Honesty-Humility outperforms Big Five Agreeableness in accounting for diverse (un)ethical behaviors such as dishonesty (Heck, Thielmann, Moshagen, & Hilbig, 2018) and counterproductive work behavior (Lee, Berry, & Gonzalez-Mule, 2019;Pletzer, Bentvelzen, Oostrom, & De Vries, 2019).…”
Section: Commentsmentioning
confidence: 99%
“…Organ (1988) identified three dimensions of OCBI, namely, altruism, conscience, and courtesy. Marcus et al (2007) pointed out that honesty/humility predicts a strong moral conscience that induces prosocial and ethical behaviors toward others (Oh et al, 2014) and prompts a moral obligation to help (altruism) and respect others even when one can be exploited by them (courtesy) (Lee et al, 2019). Ashton and Lee (2007) suggested that the honesty/humility construct evokes reciprocal altruism as a motive for prosocial behavior of those observing the trait in a significant other.…”
Section: Honesty/humility Moral Identity Centrality and Ocbimentioning
confidence: 99%
“…The HEXACO model encompasses six trait dimensions: honesty-humility, emotionality, extraversion, agreeableness versus anger (in the following termed agreeableness ), conscientiousness, and openness to experience (in the following termed openness ). Research relying on the HEXACO model as a framework of individual differences has heavily increased in recent years, not only in personality psychology (e.g., Ruchensky, Donnellan, & Edens, 2018) but also across (psychological) disciplines such as behavioral economics (e.g., Thielmann, Spadaro, & Balliet, 2020; Zhao & Smillie, 2015), clinical psychology (e.g., Gaughan, Miller, & Lynam, 2012), educational psychology (e.g., Allgaier, Zettler, Wagner, Püttmann, & Trautwein, 2015; McAbee, Casillas, Way, & Guo, 2019), political psychology (e.g., Lee, Ashton, Griep, & Edmonds, 2018), and work and organizational psychology (e.g., Lee, Berry, & Gonzalez-Mulé, 2019; Pletzer, Bentvelzen, Oostrom, & de Vries, 2019).…”
mentioning
confidence: 99%